Measurement equipment system by using digital signal processor / Shahrulnizam Salleh - Salleh, Shahrulnizam (2001)
This project discusses about a development of a measurement equipment system. The development of this system involved the development of sensor board to detect voltage and current waveforms in form of sinusoidal from the input signal. It also involves the development of Slave Board and Xilinx Field Programmable Gate Array (FPGA). The sub components of the slave board comprise EEPROM ADC. RAM, Sample and Hold Chips and Multiplexer. All the operation in the slave board is controlled by Xilinx FPGA which offer design flexibility and adaptability with optimize device utilization. Xilinx will be downloaded with design circuit that gives command to control process in the slave board. Start from design circuit until downloading process, all the process done using Xilinx software tools. All the operation of the system is controlled and monitored by the computer through the digital signal processing (DSP) software. The software and hardware developed provide suitable for research in IC"s design and DSP breakthrough